What's occurring? Ultrasonic signature whistle use in Welsh bottlenose dolphins (Tursiops truncatus). Issue 1 (2nd January 2017) - Hiley, Helen M.; Perry, Sarah; Hartley, Steve; King, Stephanie L.
Abstract: Animal communication signals are diverse. The types of sounds that animals produce, and the way that information is encoded in those sounds, not only varies between species but can also vary geographically within a species. Therefore, an understanding of the vocal repertoire at the population level is important for providing insight into regional differences in vocal communication signals. One species whose vocal repertoire has received considerable attention is the bottlenose dolphin. This species is well known for its use of individually distinctive identity signals, known as signature whistles. Bottlenose dolphins use their signature whistles to broadcast their identity and to maintain contact with social companions. Signature whistles are not innate, but are learnt signals that develop within the first few months of an animal's life. It is therefore unsurprising that studies which have characterized signature whistles in wild populations of bottlenose dolphins have provided evidence of geographic variation in signature whistle structure. Here, we describe the occurrence of signature whistles in a previously unexplored wild population of bottlenose dolphins in Cardigan Bay, Wales. We present the first occurrence of a signature whistle with an ultrasonic fundamental frequency component (>30 kHz), a frequency band that was not thought to be utilized by this species for whistle communication. We also describe the occurrence of an ultrasonic non-signature whistle. Our findings highlight the importance of conducting regional studies in order to fully quantify a species' vocal repertoire, and call into question the efficacy of those studies that use restricted sampling rates.